2020
DOI: 10.1016/j.celrep.2020.108521
|View full text |Cite
|
Sign up to set email alerts
|

A Multicellular Network Mechanism for Temperature-Robust Food Sensing

Abstract: Highlights d C. elegans' ability to modulate lifespan in response to food is robust to temperature d Robustness requires TGF-b and serotonin signaling in a neuronal network d Specific regulations in the neuronal network change sign with temperature d Temperature-dependent regulations compensate for temperature

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
(139 reference statements)
0
1
0
Order By: Relevance
“…Because food levels affected the H 2 O 2 -induced food leaving behavior of C. elegans , we speculated that this behavior may be regulated by the neurotransmitter serotonin. Expression of the serotonin biosynthetic tryptophan hydroxylase gene tph-1 increases with food (Cunningham et al, 2012; Entchev et al, 2015; Liang et al, 2006; Patel et al, 2020; Sze et al, 2000; Zheng et al, 2005) and serotonin regulates many food-related behaviors (Liang et al, 2006; Melo and Ruvkun, 2012; Sze et al, 2000; Zheng et al, 2005). We found that tph-1(mg280) null mutants, which specifically lack serotonin (Sze et al, 2000), were more likely than wild-type animals to leave a lawn of E. coli JI377 when 1 mM H 2 O 2 was added to the environment (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…Because food levels affected the H 2 O 2 -induced food leaving behavior of C. elegans , we speculated that this behavior may be regulated by the neurotransmitter serotonin. Expression of the serotonin biosynthetic tryptophan hydroxylase gene tph-1 increases with food (Cunningham et al, 2012; Entchev et al, 2015; Liang et al, 2006; Patel et al, 2020; Sze et al, 2000; Zheng et al, 2005) and serotonin regulates many food-related behaviors (Liang et al, 2006; Melo and Ruvkun, 2012; Sze et al, 2000; Zheng et al, 2005). We found that tph-1(mg280) null mutants, which specifically lack serotonin (Sze et al, 2000), were more likely than wild-type animals to leave a lawn of E. coli JI377 when 1 mM H 2 O 2 was added to the environment (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%